Animal Artistic Agency in Performative Interspecies Art in the Twenty-First Century - Ullrich, Jessica (Boletín de Arte, 2019)
Traditional aesthetic places non-human animals in nature and not in culture. Non-human animals are generally considered to be artless beings without any urge or capacity to create aesthetic objects. To the contrary, the ability and the need to produce art is perceived as one of the last thresholds of humanity. Nevertheless, in the last decades more and more contemporary artists involve living non-human animals in artistic productions. By doing so they declare some non-human animals to be co-authors of artworks and trust in their creative agency. But is it legitimate to take animal contributions to installations, sculptures, video works, or paintings seriously? Can non-human animals be aesthetic actors in their own right? The text focuses on interspecies artworks that only come into existence with the help of non-human animals. While it seems clear that the participating non-human animals display some form of agency, it is debatable if they can be called artists.